Cardiomyocytes induced from hiPSCs by well-defined compounds have therapeutic potential in heart failure by secreting PDGF-BB - Hongmei Li; Fenfang Wu; Guangrui Huang; Di Wu; Ting Wang; Xiashuang Wang; Kai Wang; Yuyin Feng; Anlong Xu (Signal Transduction and Targeted Therapy, 2022)
Abstract Recent studies have suggested that transplant of hiPS-CMs is a promising approach for treating heart failure. However, the optimally clinical benefits have been hampered by the immature nature of the hiPS-CMs, and the hiPS-CMs-secreted proteins contributing to the repair of cardiomyocytes remain largely unidentified. Here, we established a saponin+ compound optimally induced system to generate hiPS-CMs with stable functional attributes in vitro and transplanted in heart failure mice. Our study showed enhanced therapeutic effects of optimally induced hiPS-CMs by attenuating cardiac remodeling and dysfunction, these beneficial effects were concomitant with reduced cardiomyocytes death and increased angiogenesis. Moreover, the optimally induced hiPS-CMs could gathering to the injured heart and secret an abundant PDGF-BB. The reparative effect of the optimally induced hiPS-CMs in the hypoxia-injured HCMs was mimicked by PDGF-BB but inhibited by PDGF-BB neutralizing antibody, which was accompanied by the changed expression of p-PI3K and p-Akt proteins. It is highly possible that the PI3K/Akt pathway is regulated by the PDGF-BB secreted from the compound induced hiPS-CMs to achieve a longer lasting myocardial repair effect compared with the standard induced hiPS-CMs. Taken together, our data strongly implicate that the compound induced hiPS-CMs promote the recovery of injured hearts via paracrine action. In this process, the paracrine factor PDGF-BB derived from the compound induced hiPS-CMs reduces isoproterenol-induced adverse cardiac remodeling, which is associated with improved cardiac function, and these effects are mediated by the PI3K/Akt pathway, suggesting that the optimally induced hiPS-CMs may serve as a new promising cell therapy for clinical applications.